Validation of a questionnaire to measure the expectations and interests labor in the university student - Fernández-Jiménez, Miguel Ángel; Mena-Rodríguez, Esther; Gómez-Carrillo, Victoria del Rocío (New Trends and Issues Proceedings on Humanities and Social Sciences, 2019)
The establishment of the European Higher Education Area (EHEA) has promoted an attempt to design a syllabus that is more related to the world of work. There is evidence to suggest that the transfer of skills that should be acquired by students throughout their university courses is not carried out in an appropriate way that prepares them for working life. In view of this, it is essential to understand university students’ perceptions and assessments of relevant aspects of their entry into the labour market. To this end, an instrument was designed to evaluate university students’ perception and assessment of future employment. In order to verify the reliability and measurement validity of the questionnaire, a pilot study was carried out with a sample of a total of 220 university students. The analyses carried out have proved the quality of the instrument in terms of adequate reliability and measurement validity.
Keywords: Profesores - Formación profesional; Evaluation questionnaire; Labour insertion; Labour expectations; Reliability; Validity